Stochastic Search Genetic Algorithm Approximation of Input Signals in Native Neuronal Networks - Anisenia, Andrei (Université d'Ottawa / University of Ottawa, 2013)
The present work investigates the applicability of Genetic Algorithms (GA) to the problem of signal propagation in Native Neuronal Networks (NNNs). These networks are comprised of neurons, some of which receive input signals. The signals propagate though the network by transmission between neurons. The research focuses on the regeneration of the output signal of the network without knowing the original input signal. The computational complexity of the problem is prohibitive for the exact computation. We propose to use a heuristic approach called Genetic Algorithm. Three algorithms are developed, based on the GA technique. The developed algorithms are tested on two different networks with varying input signals. The results obtained from the testing indicate significantly better performance of the developed algorithms compared to the Uniform Random Search (URS) technique, which is used as a control group. The importance of the research is in the demonstration of the ability of GA-based algorithms to successfully solve the problem at hand.
Keywords: stochastic search; Genetic Algorithm; neuronal networks; neuron; signals; graph algoritms